Determination of LD50 for Streptococcus agalactiae and Staphylococcus aureus infections in tilapia - Mansor, Nur Nazifah; Nawi, Mohd Firdaus; Mohd Yusoff, Md Sabri; Abdullah, Siti Zahrah; Saad, Mohd Zamri (Veterinary Association Malaysia, 2011)
One hundred and sixty fingerlings and 80 adult tilapias were experimentally infected with Streptococcus agalactiae and Stapylococcus aureus to determine their LDso. Four concentrations of Streptococcus agalactiae (109, 108,107, 106 CFU/mL) were used in this experimental infection. These tilapias were divided into 4 groups of 40 fingerlings and 20 adults per group. Groups 1, 2, 3 and 4 of the fingerlings were exposed to 109, 10,107, 106 CFU/mL of S. agalactiae by immersion in 2 L inoculum solution for 20 min. Similarly, the adult groups were exposed to the same concentrations of S. agalactiae but by intraperitoneal injection at the rate of 1 mL of the inoculum per gram. Similar procedures were repeated using exposure to Staphylococcus aureus alone or a combination of S. agalactiae and S. aureus. All test groups were observed for signs of infections. On Day 7 post-infection (pi), all fish that were still alive were humanely killed. The LDso of the adult tilapia that were exposed to S. agalactiae, S. aureus or mixed infection was 2.3884 x 107,2.8151 X 108 , and 4.2409 x io', respectively. For the fingerling groups, the LDso for S. agalactiae, S. aureus, and mixed infection was 2.9242 x 1020,2.8665 x 1017 , and 4.9748 x IO!', respectively. Experimental infection in adults could be established within 12 h post-injection to 6.3 x 109 CFU per mL and 9.7 x 109 CFU per mL of S. agalactiae and S. aureus, respectively. For fingerlings, infection could be established within 72 h following bath immersion to 6.3 x 109 CFU per mL and 9.7 x 109 CFU per mL of S. agalactiae and S. aureus, respectively.